Knowledge Transfer Practices: A Means of Sustainable Career Development among Non-Academic Senior Members in Ghana - Kissi-Abrokwah, Bernard; Anontise, Isaac Aboyom; Kodua-Ntim, Kwame; Adugbila, Emmmanuel Junior; Mensah, Grace (Technium Social Sciences Journal, 2022)
The goal of this article is to look into how knowledge transfer practices might help non-academic senior members in Ghana maintain their career progress. The research was founded on interpretive philosophical assumptions, and a multiple case study design was employed to gain a comprehensive understanding of knowledge transfer methods among non-academic senior members of Ghanaian universities. Non-academic senior members of the Kwame Nkrumah University of Science and Technology (KNUST) and University of Cape Coast (UCC) and University of Ghana (UG) make up the study's population. The non-academic senior members of the study were chosen from fifteen (15) colleges within the institutions, and data was acquired through semi-structured interviews. The data was analyzed using thematic analysis. The results show that face-to-face interaction, after-action reviews, discussion forums, documentation, workshops, brainstorming and seminars were the most common methods for knowledge transfer. Non-academic senior members benefit from this type of information transfer in their career paths and development. Institutions should build up a knowledge portal where personnel may readily access material from other units or sections within their context, according to the recommendations.